Identintas Budaya Dan Kuliner Yogyakarta Sebagai Gastronomi Dan Perspektif Pariwisata Yang Berkelanjutan - Fauzi Achmad Riyadi; Dimas Aryo Putro; Asep Parantika (Peneliti.net, 2023)
Culinary tourism is not spared from the right culture to develop sustainable tourism in Yogyakarta. Culinary tours in Yogyakarta include Gudeg Yogyakarta, Soto Lenthok, Bakpia Pathuk and many others. In addition, there are several cultural tours such as sekatenan, grebeg, tumplak diamonds and others. Gastronomy is basically closely related to culinary and cultural tourism because it can support tourist attractions in Yogyakarta. This research is to explain the identity of cultural and culinary development in Yogyakarta as well as the perspective and strategy of tourism towards a sustainable culinary culture in Yogyakarta. This research is a qualitative descriptive research and literature study method, which aims to explain the culture and cuisine of Yogyakarta and develop it as a cultural and culinary tourist attraction. This research focuses on Yogyakarta cultural and culinary identity as a gastronomic and sustainable tourism perspective